Forecasting the Retirement Age - Bravo, Jorge M. (2022)
ravo, J. M., & Ayuso, M. (2021). Forecasting the Retirement Age: A Bayesian Model Ensemble Approach. In Á. Rocha, H. Adeli, G. Dzemyda, F. Moreira, & A. M. R. Correia (Eds.), Trends and Applications in Information Systems and Technologies (pp. 123-135). (Advances in Intelligent Systems and Computing; Vol. 1365 AIST). Springer Science and Business Media Deutschland GmbH. https://doi.org/10.1007/978-3-030-72657-7_12